Video conferencing and multimodal expression of voice: Children's conversations using Skype for second language development in a telecollaborative setting. (February 2017) - Austin, Nick; Hampel, Regine; Kukulska-Hulme, Agnes
Abstract: This article explores how voice is expressed in a telecollaborative project using Skype to connect two groups of primary age English language learners across two countries. Voice is understood as the ways in which language and other semiotic means are used for communication (Blommaert, 2008). This theoretical view frames the qualitative study into how voice is expressed materially involving tools such as verbal language, body language, technology, and the spatial and temporal dimensions within which the children's conversation happens. A methodology for analysing the video recorded data was developed using Scollon and Scollon's concept of geosemiotics. This method of analysis investigates how language is materially assembled through interaction with others in the physical world. The study shows that telecollaborative conversations create particular conditions which affect the ways children express their voice. The implications discussed in the conclusion have the potential to initiate wider discussion in the context of early childhood education and language learning concerning the importance of a multimodal perspective on how children express voice to support their communication when using video conferencing.